Problematic internet use and spiritual well-being in a group of Romanian adolescents - Alexandra-Simona Vlad (Journal of Educational Studies)
The spiritual well-being of adolescents and their problematic use of Internet have been addressed in various forms in recent years, especially with the expanding use of technology. The specificity of this paper is that it puts together, in a process of interdependence, the two concepts, trying to observe to what extent the spiritual well-being of adolescents is related to the excessive use of new technologies. The purposes of the study were to measure the problematic internet use and the spiritual well-being in adolescents and to determine the relationship between these two constructs. The design was non-experimental, correlational, ex post facto. The research took place at the beginning of the school year 2023-2024 in one Seventh-day Adventist school, at the Muntenia Conference, were 62 high school students aged between 14 and 16, participated by filling out two instruments: (a) the Spiritual Well-being Scale, Romanian Children’s Version, and (b) the Problematic Internet Use Questionnaire, designed by Thatcher and Goolam (2005), and adapted for Romanian population. Correlation coefficients were calculated using Spearman’s rho. The results show that no significant correlation was observed between both constructs or between their factors, but a significant negative correlation was obtained between certain items belonging to these two different instruments. For instance, it was found that students who have problems with Internet have less interest in helping others and that students who try to escape problems through Internet believe and trust God less. There are also differences between genders in terms of spiritual well-being. In conclusion, these results are useful for both parents and educators to find ways of helping teenagers consider an appropriate use of the internet and thus support them in focusing on their relationship with God and others.